Intermediates derived from p-terphenyl in the methyltributylammonium bis[(trifluoromethyl)sulfonyl]imide ionic liquid saturated with carbon dioxide: Pulse radiolysis study - Kocia Rafał (Nukleonika, 2023)
Radiation-induced processes in ionic liquid (IL) methyltributylammonium bis[(trifluoromethyl)sulfonyl] imide ([MeBu3N][NTf2]) solutions containing p-terphenyl (TP) and saturated with carbon dioxide (CO2) were studied using nanosecond pulse radiolysis technique with UV-vis detection. The transient absorption spectra generated in these solutions were assigned to TP radical anions (TP•−) and triplet excited states (3TP*). Saturation of [MeBu3N][NTf2] solutions with carbon dioxide efficiently takes out presolvated electrons (epresolv−)( {{\rm{e}}_{{\rm{presolv}}}^ - } ) and solvated electrons (esolv−)( {{\rm{e}}_{{\rm{solv}}}^ - } ) . On the other hand CO2 is not a scavenger of excited states of TP (1TP*, 3TP*), which in the reaction with triethylamine (TEA) leads to the formation of TP•−.